2022
DOI: 10.1111/boc.202100086
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide increases exosomes secretion from endothelial progenitor cells by toll‐like receptor 4 dependent mechanism

Abstract: Background Information Endothelial progenitor cells (EPCs) can exert angiogenic effects by a paracrine mechanism, where exosomes work as an important mediator. Recent studies reported functional expression of toll‐like receptor (TLR) 4 on human EPCs and dose‐dependent effects of lipopolysaccharide (LPS) on EPC angiogenic properties. To study the effects of TLR4/LPS signaling on EPC‐derived exosomes (Exo) and clarify the mechanism, we investigated the role of LPS on exosomes secretion from human EPCs and tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…shown that an overload of cytosolic Ca 2+ due to either release from the intracellular Ca 2+ store or influx from the extracellular milieu facilitates exosome biogenesis in both physiological and pathological conditions [97,171] (Fig. 6A).…”
Section: Ca 2+ Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…shown that an overload of cytosolic Ca 2+ due to either release from the intracellular Ca 2+ store or influx from the extracellular milieu facilitates exosome biogenesis in both physiological and pathological conditions [97,171] (Fig. 6A).…”
Section: Ca 2+ Signalingmentioning
confidence: 99%
“…Dysregulation of Ca 2+ signaling and altered levels of intracellular Ca 2+ are involved in a plethora of processes in carcinogenesis, progression and chemoresistance of multiple cancer cell types [ 170 ]. Mounting evidence has shown that an overload of cytosolic Ca 2+ due to either release from the intracellular Ca 2+ store or influx from the extracellular milieu facilitates exosome biogenesis in both physiological and pathological conditions [ 97 , 171 ] (Fig. 6 A).…”
Section: Introductionmentioning
confidence: 99%